Endotoxin Predictors and Associated Respiratory Outcomes Differ with Climate Regions in the U.S - Mendy, Angelico (Environ Int, 2017)
RATIONALE: Although endotoxin is a recognized cause of environmental lung disease, how its relationship with respiratory outcomes varies with climate is unknown. OBJECTIVE: To examine the endotoxin predictors as well as endotoxin association with asthma, wheeze, and sensitization to inhalant allergens in various US climate regions. METHODS: We analyzed data on 6,963 participants in the National Health and Nutrition Examination Survey. Endotoxin measurements of house dust from bedroom floor and bedding were performed at the University of Iowa. Linear and logistic regression analyses were used to identify endotoxin predictors and assess endotoxin association with health outcomes. RESULTS: The overall median house dust endotoxin was 16.2 EU/mg; it was higher in mixed-dry/hot-dry regions (19.7 EU/mg) and lower in mixed-humid/marine areas (14.8 EU/mg). Endotoxin predictors and endotoxin association with health outcomes significantly differed across climate regions. In subarctic/very cold/cold regions, log(10)-endotoxin was significantly associated with higher prevalence of wheeze outcomes (OR:1.48, 95% CI:1.19–1.85 for any wheeze, OR:1.48, 95% CI:1.22–1.80 for exercise-induced wheeze, OR:1.50, 95% CI:1.13–1.98 for prescription medication for wheeze, and OR:1.95, 95% CI:1.50–2.54 for doctor/ER visit for wheeze). In hot-humid regions, log(10)-endotoxin was positively associated with any wheeze (OR:1.66, 95% CI:1.04–2.65) and current asthma (OR:1.56, 95% CI:1.11–2.18), but negatively with sensitization to any inhalant allergens (OR:0.83, 95% CI:0.74–0.92). CONCLUSION: Endotoxin predictors and endotoxin association with asthma and wheeze differ across U.S. climate regions. Endotoxin is associated positively with wheeze or asthma in cold and hot-humid regions, but negatively with sensitization to inhalant allergens in hot-humid climates.